2010
DOI: 10.1111/j.1574-6976.2009.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA genes in eukaryotic microorganisms: witnesses of phylogeny?

Abstract: The study of genomic organization and regulatory elements of rRNA genes in metazoan paradigmatic organisms has led to the most accepted model of rRNA gene organization in eukaryotes. Nevertheless, the rRNA genes of microbial eukaryotes have also been studied in considerable detail and their atypical structures have been considered as exceptions. However, it is likely that these organisms have preserved variations in the organization of a versatile gene that may be seen as living records of evolution. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 236 publications
(172 reference statements)
0
62
0
4
Order By: Relevance
“…However, one of the drawbacks of the DGGE technique is the fact that the number of rRNA genes per chromosome equivalent differs widely in bacteria (27). In addition, heterogeneous copies of rRNA gene operons exist for both bacteria (37) and fungi (49), so that different bands may belong to the same species.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the drawbacks of the DGGE technique is the fact that the number of rRNA genes per chromosome equivalent differs widely in bacteria (27). In addition, heterogeneous copies of rRNA gene operons exist for both bacteria (37) and fungi (49), so that different bands may belong to the same species.…”
Section: Discussionmentioning
confidence: 99%
“…The rDNA regulatory elements are generally located within this region and include the TSP, the upstream control element (UCE), the promoter, enhancer regions, intergenic promoters and the transcription terminator. In most organisms, the ribosomal genes are grouped in tandem, and T. vaginalis has approximately 14 copies of this gene cluster [1]. Using genome sequencing data [18], we compared the larger rDNA contigs and found that the different copies of the rDNA sequence were almost identical.…”
Section: Strategy and Design Of A Transcriptional Reporter System Formentioning
confidence: 99%
“…Among protozoan organisms, there is enormous diversity in sequence and gene arrangement. Each transcriptional unit is separated by intergenic sequences that vary in length among organisms, ranging from 2 to 30 kbp [1]. Both the promoter and terminator sequences are located within this intergenic region.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence variations of internal transcribed spacers (ITS1 and ITS2) of 35S rDNA have been variously used as a molecular tool for species identification in eukaryotic organisms (Marinucci et al 1999;Wilkerson et al 2004;Torres-Machorro et al 2009). We designed a pair of conserved primers (18SF and 28SR1) from rDNA sequences of 22 diatom species reported in the GenBank database (see below).…”
Section: Amplification Of the Rdna Sequencesmentioning
confidence: 99%